Strategi Tokoh Adat Dalam Meningkatkan Pemaham - Moh. Lukman Hakim; Sugiatno Sugiatno; Eka Yanuarti3 Yanuarti; Idi Warsah (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: Traditional Leaders’ Strategies In Improving Islmic Understanding Of SAD (Suku Anak Dalam) ChildrenThis study aimed to find out a depiction of traditional leaders’ strategies in improving children's understanding of Islam in the tribe called SAD (Suku Anak Dalam) in Sungai Jernih Village, Muratara District, South Sumatra. The key informants of this study were the traditional leaders in the village, and additional (secondary) informants were religious instructors and village officials. Data were collected through interview and observation techniques, and the data analysis comprised data selection, data presentation, verification, and conclusion drawing. This study obtained the following conclusions: The strategies carried out by traditional leaders in improving religious understanding of the Suku Anak Dalam (SAD) Children encompassed: 1) establishing houses of worship for Muslims: 2. Activating routinely religious programs in the aforesaid places of worship; and 3) Establishing a religion-based school, namely Madrasah Ibtidaiyah Darussalam.